2023
DOI: 10.3390/ijms241512285
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Unveils the Effective Interaction of B-RAF Inhibitors with Rare B-RAF Insertion Variants

Maria Chiara Scaini,
Luisa Piccin,
Davide Bassani
et al.

Abstract: The Food and Drug Administration (FDA) has approved MAPK inhibitors as a treatment for melanoma patients carrying a mutation in codon V600 of the BRAF gene exclusively. However, BRAF mutations outside the V600 codon may occur in a small percentage of melanomas. Although these rare variants may cause B-RAF activation, their predictive response to B-RAF inhibitor treatments is still poorly understood. We exploited an integrated approach for mutation detection, tumor evolution tracking, and assessment of response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…37 A recent report using in silico ligand-based homology modeling demonstrated that dabrafenib could adeptly bind to BRAF Thr599dup in a manner similar to that in which it binds to BRAF V600E . 21 Of note, we also showed that dimerization of BRAF Thr599dup with WT BRAF or WT CRAF was not required to exert oncogenic functions through the genetic knockout of endogenous BRAF or CRAF in Ba/F3 cells. Furthermore, we revealed that mutant-mutant BRAF dimerization was not required for BRAF Thr599dup to signal through introduction of the additional R509H mutation, leading to the lack of intact DIF.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…37 A recent report using in silico ligand-based homology modeling demonstrated that dabrafenib could adeptly bind to BRAF Thr599dup in a manner similar to that in which it binds to BRAF V600E . 21 Of note, we also showed that dimerization of BRAF Thr599dup with WT BRAF or WT CRAF was not required to exert oncogenic functions through the genetic knockout of endogenous BRAF or CRAF in Ba/F3 cells. Furthermore, we revealed that mutant-mutant BRAF dimerization was not required for BRAF Thr599dup to signal through introduction of the additional R509H mutation, leading to the lack of intact DIF.…”
Section: Discussionmentioning
confidence: 60%
“…This mutation has been detected in 2.8% (one of 36) of BRAF-mutant NSCLC, 0.6% (two of 347) of BRAF-mutant thyroid cancer, 3.1% (three of 96) of BRAFmutant nervous system cancer, and 0.24% (eight of 3,119) of all melanomas reported in the AACR GENIE cohort. 6,8,18,19 Although some case reports demonstrated the efficacy of combination BRAF-and MEK-targeted therapies in patients with BRAF Thr599dup -positive cancers, [19][20][21][22] the function and sensitivity of this mutant oncoprotein to targeted therapy are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%